Shifts in microbial communities in shallow lakes depending on trophic states: Feasibility as an evaluation index for eutrophication - Yi Wang; Minli Guo; Xiaolu Li; Guanglong Liu; Yumei Hua; Jianwei Zhao; Arnaud Huguet; Suxia Li (Ecological Indicators, 2022)
Microbial communities are an important component of aquatic ecosystems. They play active roles in the biogeochemical cycles of organic matter and nutrients to maintain the health and stability of aquatic ecosystems. In the present study, the shifts in microbial communities in overlying water of 15 shallow lakes with different trophic states in Hubei Province (China) were assessed using Illumina MiSeq sequencing technology. The results revealed that the proteobacteria to be the most abundant phylum in lakes with different trophic states. Mesotrophic lakes were found to be similar to moderately eutrophic lakes in terms of the microbial community composition, the interrelation between microbial communities, and expression level of metabolic pathways. In mesotrophic and moderately eutrophic lakes, Bacillus and Pseudomonas were the dominant genera in overlying water. In lakes with less eutrophication, the microbial diversity tended to be higher. Lightly eutrophic lakes had the most microbial species; however, the interaction between microorganisms was the weakest in these lakes and the internal steady-state balance of the lakes was most susceptible to being broken. These results indicate that lightly eutrophication may be one of the most unstable transition states in the eutrophication process. Particulate organic matter, chlorophyll-a, and ammonium nitrogen were the main drivers affecting the distribution of microbial communities in the overlying water of lakes with different trophic states. In addition, the correlation between microbial communities and lake trophic states was analyzed based on the bacterial eutrophic index (BEI). An obvious positive correlation was noted between BEI and the trophic level index (TLI), indicating that microbial communities could play a role as biological factors in the evaluation of lake trophic states along with other known physicochemical indicators.